Methods for Calculating the Socio-Economic Losses Caused by Industrial Accidents - Imamovich, Makhmatkulov Nurilla; Qizi, Khasanov Labor Abdulla (Lembaga Yasin AlSys, 2025)
This article presents and summarizes traditional methods used to calculate the socio-economic losses resulting from accidents that occur in technical or technological processes across various sectors of the economy. It describes how these approaches are applied to evaluate the consequences of industrial hazards for safety, injuries, emergencies, and the use of labor resources.